ANALISIS DRAMA MASTODON DAN BURUNG KONDOR KARYA W.S. RENDRA MENGGUNAKAN PENDEKATAN STRUKTURALISME GENETIK LUCIEN GOLDMANN - Dina Alistri; Mya Mulyany; Nazwa Agnia Teja Respati; Rista Septiwianti Septiwianti; Roby Rahmat Kausar; Tri Handoyo; Adita Widara Putra (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
Drama is a type of literary work that has a distinctive characteristic, namely combining literary elements and performing arts. This study analyzed the drama